Energetic mapping of oxide traps in MoS2 field-effect transistors. (8th June 2017) - Illarionov, Yury Yu; Knobloch, Theresia; Waltl, Michael; Rzepa, Gerhard; Pospischil, Andreas; Polyushkin, Dmitry K; Furchi, Marco M; Mueller, Thomas; Grasser, Tibor
Abstract: The performance of MoS2 transistors is strongly affected by charge trapping in oxide traps with very broad distributions of time constants. These defects degrade the mobility and additionally lead to the hysteresis of the gate transfer characteristics, which presents a crucial performance and reliability issue for these new technologies. Here we perform a detailed study of the hysteresis in double-gated MoS2 FETs and show that this issue is nothing else than a combination of threshold voltage shifts resulting from positive and negative bias-temperature instabilities. While these instabilities are well known from silicon devices, they are even more important in 2D devices given the considerably larger defect densities. Most importantly, the magnitudes of these threshold voltage shifts depend strongly on the density and energetic alignment of the active oxide traps. Based on this, we introduce the incremental hysteresis sweep method which allows for an accurate mapping of these defects and extract their energy distributions from simulations. By applying our method to analyze the impact of oxide traps situated in the Al2 O3 top gate of several devices, we confirm its versatility. Since all 2D devices investigated so far suffer from a similar hysteresis behavior, the incremental hysteresis sweep method provides a unique and powerful way for the detailed characterization of their defect bands.